“Mission Matters”: The mediation effect of organizational trust between perceived corporate social responsibility and organizational identification, and moderation effect of mission commitment - Kim, ByungJik; Ji, WonKoo; Jeon, SangGil (Korean Journal of Industrial and Organizational Psychology, 2015)
The current study tested whether organizational trust mediated the relationship between perceived corporate social responsibility(CSR) and organizational identification(OI). In order to investigate the hypotheses, 11843 employees in private bank were sampled across two time points. Using structural equation modeling(SEM), we set moderated mediation model which elaborately delves into the significance of the hypotheses. The results showed that organizational trust mediated the link between perceived CSR and OI. In addition, the relationship between perceived CSR and organizational trust was moderated by mission commitment. The implications and limitations, and suggestions for future research were discussed.